Early childhood interventions : proven results, future promise - Karoly, Lynn A., 1961- (Rand, 2005)
Parents, policymakers, business leaders, and the general public increasingly recognize the importance of the first few years in the life of a child for promoting healthy physical, emotional, social, and intellectual development. Nonetheless, many children face deficiencies between ages 0 and 5 that can impede their ability to develop to their fullest potential. The PNC Grow Up Great initiative, a program financed by PNC Financial, Inc., asked RAND to prepare a thorough, objective review and synthesis of current research that addresses the potential for various forms of early childhood intervention to improve outcomes for participating children and their families. The authors consider the potential consequences of not investing additional resources in the lives of children, the range of early intervention programs, the demonstrated benefits of interventions with high-quality evaluations, the features associated with successful programs, and the returns to society associated with investing early in the lives of disadvantaged children. Their findings indicate that a body of sound research exists that can guide resource allocation decisions. This evidence base sheds light on the types of programs that have been demonstrated to be effective, the features associated with effective programs, and the potential for returns to society that exceed the resources invested in program delivery.